Silius Italicus on the Battle of Cannae: a Commentary on "Punica 10" - Dominik, William J. (Exemplaria Classica, 2019)
R. JoyLittlewood(ed., trans.), A Commentary on Silius Italicus’ Punica 10: Edited with Introduction, Translation, and Commentary, Oxford- New York: Oxford University Press, 2017, lxxix+265 pp., £75.00, ISBN 978-0- 19-871381-4.